2016
DOI: 10.1503/cjs.013415
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the complexities of shared decision-making in cancer: a qualitative study of the perspectives of patients undergoing colorectal surgery

Abstract: Background: Decisions leading up to surgery are fraught with uncertainty owing to trade-offs between treatment effectiveness and quality of life. Past studies on shared decision-making (SDM) have focused on the physician-patient encounter, with little emphasis on familial and cultural factors. The literature is scarce in surgical oncology, with few studies using qualitative interviews. Our objective was to explore the complexities of SDM within the setting of colorectal cancer (CRC) surgery. Methods:An interdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…However, we found that more than half of the patients with AMD preferred to leave the final decision up to their doctors and played passive roles in treatment decision making. This fact about patients with AMD was different from patients with other diseases such as fractures20 or cancers21 22 who were willing to make decisions on their own. The main reason may be that most of the patients with AMD were older people who were limited by their physical, psychological and social functions.…”
Section: Discussionmentioning
confidence: 93%
“…However, we found that more than half of the patients with AMD preferred to leave the final decision up to their doctors and played passive roles in treatment decision making. This fact about patients with AMD was different from patients with other diseases such as fractures20 or cancers21 22 who were willing to make decisions on their own. The main reason may be that most of the patients with AMD were older people who were limited by their physical, psychological and social functions.…”
Section: Discussionmentioning
confidence: 93%
“…Others recently advocated that SDM in fact “needs to centre on the person, rather than the medical encounter.” Outside the consultation, patients can consider their options, consult others, or search for information, all as part of the SDM process. Indeed, ideas of patients' family members about treatment options may influence patients . Furthermore, cancer patients are known to search for information beyond consultations, eg, on the internet, in books, through other media, or by consulting others with experience with cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ideas of patients' family members about treatment options may influence patients. 28 Furthermore, cancer patients are known to search for information beyond consultations, eg, on the internet, in books, through other media, or by consulting others with experience with cancer. 16,[29][30][31] Our and others' 32 findings highlight the importance of including a so-called time out in cancer treatment decision making, with at least two consultations, to make important decisions.…”
Section: Provide Recommendation and Express Preferencementioning
confidence: 99%
“…Upon achieving data saturation (the point at which no new information that was relevant to the research question emerged), these categories were further analyzed and refined to identify overarching themes in the attitudes, perceptions and experiences of patients. [17][18][19][20] Sociodemographic and clinical data were summarized using descriptive statistics. We compared the 3 surgical modality cohorts with respect to aggregate body image and QOL scores.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one must remain sensitive to the unique decision-making preferences of each patient to align their expectations with known or possible postoperative outcomes. 20 It is also important to note that while QOL after rectal cancer surgery has been a topic of numerous studies, 6,8,[23][24][25][26][27][28] specific comparisons of all 3 surgical modalities and their impact on survivorship are yet to mature. In our study, surgical modality did not have a considerable impact on emotional and cognitive function, or symptom scales assessing GI function, defecation, psychological symptoms and pain.…”
Section: Discussionmentioning
confidence: 99%